Substantive Criminal Protection to Intangible Cultural Heritage - زيدان محمد جياد (Journal of Legal Sciences, 2019)
The cultural heritage is intangible legacy represents all froms of intellectual creativity in different fields of life. It is traditional legacy expresses on the past, and it is still inherited and connected from generation to generation. Thus, the cultural legacy could be classified as it is intellectual property due to its importance for its people. This kind of property may require protection against any violation. Therefore, this article examined the penal protection of this sert of property in the light of the current laws, in order to provide the sufficient protection to the cultural legacy.